Identification of personal factors that influence engagement in cardiac rehabilitation and interventions targeting personal factors: A scoping review protocol - Hongyu Zhang; Duygu Sezgin (PLoS ONE, 2025)
Cardiac rehabilitation effectively reduces mortality and enhances the quality of life for individuals with cardiovascular disease. Despite that, individuals’ engagement in cardiac rehabilitation remains low. Considering the significant contributions of individuals’ self-management of cardiovascular disease to their progress, it is essential to understand the personal factors that influence engagement in cardiac rehabilitation. This scoping review aims to identify and map personal factors that influence cardiac rehabilitation engagement with a specific focus on the subjective experiential dimensions of personal factors (cognitive, emotional, and behavioural). It also aims to explore interventions targeting personal factors to increase cardiac rehabilitation engagement. This review will be reported using the PRISMA-ScR checklist following the Joanna Briggs Institute (JBI) methodology. It will include peer-reviewed articles published in English from January 2004, excluding grey literature. Studies reporting adult populations aged 18 and over with cardiovascular disease and addressing personal factors or interventions to increase cardiac rehabilitation engagement, will be included. Databases for the searches will include PubMed, Embase, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Scopus, and Web of Science. The data extraction is developed by the reviewers based on JBI guidelines and relevant literature, the form will detail the characteristics of included publications, personal factors influencing cardiac rehabilitation engagement, and intervention characteristics. The data analysis will summarise descriptively the key features of the included studies and interventions, the Patient Health Engagement Model will guide the categorisation of personal factors into cognitive, emotional, and behavioural aspects, with other personal factors organised as emerging other relevant factors themes. The findings of this review will provide important evidence support for researchers, clinicians and policy makers to promote participation in cardiac rehabilitation. Within the constraints of medical and human resources, attention to personal factors can maximise the individual’s role in cardiac rehabilitation and self-management, contributing to the efficient allocation and use of resources.